Effect of thickness variation on collapse pressure of seamless pipes - Kara, Fuat; Navarro, Josef; Allwood, Robert L. (Ocean engineering, 2010)
The present paper is concerned with determining the effect of thickness variation on collapse pressure of seamless pipes. There exists extensive information on the effects external pressure has on pipelines. A substantial amount of literature deals with results of analysis, numerical modelling and testing of pipes those are gradually subject to external pressure. This knowledge has been incorporated into standards which are intended for designing linepipe operating in deepwater locations. One such example is the DNV-OS-101 ( DNV, 2007) Submarine Pipeline Systems standard. This code only addresses pipes with a nominally uniform wall thickness making it inadequate for designing seamless pipe which is prone to thickness variation arising from the manufacturing process. The DNV (2007) code effectively ignores the problem as it simply provides a vague statement regarding a conservative value of wall thickness that should be used in the design calculations. The present paper uses finite element analysis (FAE) modelling to predict the external pressure acting on the pipes. The present paper explains the manner in which FEA models will be used to study the effect wall thickness variation will have on the pressure at which the pipe will collapse. An improvement to the DNV (2007) code is then suggested by interpreting the results of the FEA models. The case study that follows provides insight on the savings the improved method is projected to offer.